Free Space Optic MIMO pada Kondisi Hujan dan Angin di Kota Pekanbaru - Muhammad Fachrul Afiansyah; Rika Susanti; Teddy Purnamirza; Fitri Amillia (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2024)
The FSO communication system is a communication system that uses the atmosphere as a propagation medium for light, which is used as an optical source to transmit data to the receiver. Due to using the atmosphere as a propagation medium causes the FSO communication system to be susceptible to signal weakening caused by varying atmospheric attenuation. So, it is necessary to conduct research on FSO performance based on atmospheric conditions. This research carried out communication design using FSO technology in Pekanbaru City, analyzing the influence of rainy weather and wind data using FSO MIMO. After analyzing and optimizing the parameters contained in the FSO device to achieve the best FSO performance. The design simulation was carried out using optisystem software for Free Space Optics (FSO) analysis using the FSO MIMO technique in rainy and windy weather in Pekanbaru City. One of the impacts of using the atmosphere as a propagation medium is large attenuation. The variables analyzed by the researchers were the rain variable and the wind variable. If the laser uses power up to 10 mW at a frequency wave of 1550 nm. The simulation results of the four-channel FSO MIMO system are able to provide a maximum beam distance of up to 2 km in rainfall conditions and 8 km in windy conditions. This value was obtained through analysis of the BER and Q-Factor values in the simulation results.Keywords - FSO-MIMO, BER, Optisystem